RESTORING THE CRITICAL POWER OF CURRICULUM STUDIES TO TRANSFORM THE SOCIETY - Subkhan, Edi (Indonesian Journal of Curriculum and Educational Technology Studies, 2019)
Curriculum Studies has evolved for years and already gain its very honorable place in the heart of education studies. Most education scholars said that curriculum is important, curriculum is the heart of education (Priestley & Philippou, 2019), as does curriculum studies. But, how this very important field of studies survive and evolve in this vulnerable and unpredictable era which neoliberal agendas dominating almost educational field around the world? We are witnessing how the culture of positivism, competition ideology, New Managerialism, and even racism and hatred, poisoning and deflect the aims of education. On the other hand, there also a crisis in curriculum studies in which curriculum seems only struggling and focusing on theoretical discourse without any significant influences on the material world. Right in this very difficult position of curriculum studies, the work of Wayne Au is significant. He wrote very important book entitled ?Critical Curriculum Studies: Education, Consciousness, and the Politics of Knowing? in 2012. Which Michael Apple in the series editor introduction said that this work is ambitious and provocative, because it seeks theoretical and epistemological foundation of critical curriculum studies that challenges many basic assumptions about curriculum (Au, 2012, p. xv). I am agree with what has Apple said and through this review book article I would say that Au?s work has huge contribution to the development of curriculum studies in this contemporary era, especially in order to become a tool to change or transform the society to be more democratic and just.